Washington View: Keeping millennials in classrooms requires time and support. (February 2016) - Ferguson, Maria
While in the process of designing a graduate course on education policy the author learns that so many students once were classroom teachers, felt called to it, but were disillusioned by what they found in schools and thus sought refuge in education policy. Schools are driving out millennials or discouraging them from entering in the first place. We should help remedy that by providing teachers with more support through giving them time and an apparatus to help them improve if we find their performance lacking. We also should stop putting them at the epicenter of the nation's education woes.